Fosfomycin resistance mechanisms in Enterobacterales: an increasing threat - Mattioni Marchetti, Vittoria; Hrabak, Jaroslav; Bitar, Ibrahim (Frontiers in Cellular and Infection Microbiology, 2023)
Antimicrobial resistance is well-known to be a global health and development threat. Due to the decrease of effective antimicrobials, re-evaluation in clinical practice of old antibiotics, as fosfomycin (FOS), have been necessary. FOS is a phosphonic acid derivate that regained interest in clinical practice for the treatment of complicated infection by multi-drug resistant (MDR) bacteria. Globally, FOS resistant Gram-negative pathogens are raising, affecting the public health, and compromising the use of the antibiotic. In particular, the increased prevalence of FOS resistance (FOSR) profiles among Enterobacterales family is concerning. Decrease in FOS effectiveness can be caused by i) alteration of FOS influx inside bacterial cell or ii) acquiring antimicrobial resistance genes. In this review, we investigate the main components implicated in FOS flow and report specific mutations that affect FOS influx inside bacterial cell and, thus, its effectiveness. FosA enzymes were identified in 1980 from Serratia marcescens but only in recent years the scientific community has started studying their spread. We summarize the global epidemiology of FosA/C2/L1-2 enzymes among Enterobacterales family. To date, 11 different variants of FosA have been reported globally. Among acquired mechanisms, FosA3 is the most spread variant in Enterobacterales, followed by FosA7 and FosA5. Based on recently published studies, we clarify and represent the molecular and genetic composition of fosA/C2 genes enviroment, analyzing the mechanisms by which such genes are slowly transmitting in emerging and high-risk clones, such as E. coli ST69 and ST131, and K. pneumoniae ST11. FOS is indicated as first line option against uncomplicated urinary tract infections and shows remarkable qualities in combination with other antibiotics. A rapid and accurate identification of FOSR type in Enterobacterales is difficult to achieve due to the lack of commercial phenotypic susceptibility tests and of rapid systems for MIC detection.